ҚОРАҚАЛПОҚ ЎҚУВЧИЛАРИНИНГ АНЪАНАВИЙ МЕҲНАТ ТАЪЛИМИ ТАМОЙИЛЛАРИ – УЛАРНИНГ МАЪНАВИЯТИ ВА АҲЛОҚИНИ ШАКЛЛАНТИРИШ МЕЗОНЛАРИ СИФАТИДА - Дошниязов, Ж.Қ. (SCIENCE and SOCIETY, 2021)
The article reveals the basic principles of the traditional labor education of the Karakalpaks, the role of labor traditions and customs in folk pedagogy, the pedagogical capabilities of the Karakalpak folk traditions of craffsmanship and fine wedle-work as a means of forming the labor skills of adolescents, and the attitude of yoth was clarified adolescents to work activity.